Pemahaman Dan Penerapan Prinsip-Prinsip Hak Asasi Manusia Dalam Operasi Polisi - Nyimas Ida Friyani, Andri Nurwandi, Adi Putra, Fitri Dwiyana, Juwita Afriyani, Kiki, (Pusdikra Publishing, 2024)
Understanding and Application of Human Rights Principles in Police Operations is the title of this research study. This study employs qualitative field research, with data being gathered through documentation and structured interviewing methods. The purpose of this study is to shed light on the challenges faced by law enforcement in their efforts to uphold human rights in society. And the study's conclusion is that Law No. 2 of 2002's article 13 on maintaining security and public order contains guidance on the comprehension and application of human rights principles in police operations.